2001
DOI: 10.1039/b101889m
|View full text |Cite
|
Sign up to set email alerts
|

The syntheses of three highly unsaturated marine lipid hydrocarbons

Abstract: Starting from (all-Z )-icosa-5,8,11,14,17-pentaenoic acid (EPA), syntheses of the naturally occurring hydrocarbons (all-Z )-henicosa-1,6,9,12,15,18-hexaene ( 1), (all-Z )-pentadeca-3,6,9,12-tetraen-1-yne (2, laurencenyne) and the corresponding 3E-isomer 3 (trans-laurencenyne) have been accomplished.Scheme 1 Reagents and conditions: i) DIBAL-H, toluene, Ϫ78 ЊC; ii) Ph 3 P᎐ ᎐ CH 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…Spectral data were in agreement with those previously reported [17]. (13) was prepared by reduction of 9 with NaBH 4 according to the literature [20]. (10).…”
Section: E6z9z12z15z-octadecapentaenal (9)supporting
confidence: 81%
See 1 more Smart Citation
“…Spectral data were in agreement with those previously reported [17]. (13) was prepared by reduction of 9 with NaBH 4 according to the literature [20]. (10).…”
Section: E6z9z12z15z-octadecapentaenal (9)supporting
confidence: 81%
“…The vinyl ketone 1 attracted our interest as part of an ongoing project utilizing the polyunsaturated fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) as starting materials for the OPEN ACCESS syntheses of compounds containing several methylene interrupted Z double bonds [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. A key reaction in this respect is the oxidative degradation of EPA and DHA to aldehydes by way of the corresponding iodolactones.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolites 923-926, found in Japanese populations of L. okamurai [192,204,779,780], are considered to be biosynthetic precursors of various C 15 non-terpenoid metabolites found in Laurencia species. Their synthesis was reported by the Yamada group in 1981 and 1986 [204,780], while another synthesis of laurencenyne (926) and its (E)-isomer 925 was later achieved by Holmeide et al starting from eicosapentaenoic acid [781]. A Japanese L. nipponica population afforded a mixture of optical isomers ((6R,7R) and (6S,7S)) of (E)-(942) and (Z)-laurediol (943), along with their diacetates 945 and 946, respectively [738].…”
Section: Linear Acetogeninsmentioning
confidence: 96%
“…Inhibitors 1 and 2 were identified as (6Z,9Z,12Z,15Z)-1,6,9,12,15-henicosapentaene 15 (HEP, Figure 1) and (6Z,9Z,12Z,15Z,18Z)--1,6,9,12,15,18-henicosahexaene 14 (HEH, Figure 1), respectively, by their spectral data, 16 compared with the literature data. [17][18][19][20] Stereostructures of double bonds of 1 and 2 were deduced to be all Z configurations from the 13 C NMR data (δ 25.63-25.64 for 1; δ 25.52-25.64 for 2) for the allylic positions in 1,4-pentadiene moieties of them. Pfeffer et al 21 reported that the 13 C NMR data of δ 25.7, 30.5, and 35.7 for the allylic positions in 1,4-pentadiene moieties of polyunsaturated fatty acid residues were assigned as Z,Z-, Z,E-, and E,E-isomers, respectively.…”
mentioning
confidence: 99%